2022
DOI: 10.1186/s40001-022-00733-9
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune inflammation index and system inflammation response index are potential biomarkers of atrial fibrillation among the patients presenting with ischemic stroke

Abstract: Background Chronic inflammatory disorders in atrial fibrillation (AF) contribute to the onset of ischemic stroke. Systemic immune inflammation index (SIII) and system inflammation response index (SIRI) are the two novel and convenient measurements that are positively associated with body inflammation. However, little is known regarding the association between SIII/SIRI with the presence of AF among the patients with ischemic stroke. Methods A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…SIRI comprises the absolute number of neutrophils, monocytes, and lymphocytes [ 40 ]. In a 10-year observation, SIRI was found to have an association with CVD occurrence [ 41 ] and an increased risk of supraventricular tachycardia in patients with a history of stroke [ 42 ]. In patients who underwent percutaneous coronary intervention (PCI) due to ACS, SIRI was an independent predictor of MACE [ 29 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…SIRI comprises the absolute number of neutrophils, monocytes, and lymphocytes [ 40 ]. In a 10-year observation, SIRI was found to have an association with CVD occurrence [ 41 ] and an increased risk of supraventricular tachycardia in patients with a history of stroke [ 42 ]. In patients who underwent percutaneous coronary intervention (PCI) due to ACS, SIRI was an independent predictor of MACE [ 29 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…New biomarkers using three cell lines, the systemic inflammatory response index (SIRI), and the systemic inflammatory reaction index (SII) were previously evaluated in the determination of the outcome of neoplastic diseases [ 19 , 20 ]. In cardiology, high SIRI was correlated with an increased risk of ACS in patients with chest pain [ 21 ], supraventricular tachycardia in patients with stroke [ 22 ], and major adverse cardiovascular events (MACE) in patients after ACS treated with percutaneous intervention (PCI) [ 23 ]. SII was associated with an increased risk of MACE in patients with heart failure [ 24 ], after cardiosurgery [ 25 , 26 , 27 , 28 ], and after PCI [ 23 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several inflammatory indexes, such as, C-reactive protein, NLR, interleukins, have been demonstrated to be predictive of short- or long-term prognosis in patients with STEMI [ 24 28 ]. Recent studies had demonstrated the positive relationship between SIRI and prognosis information in different subject cohorts [ 14 16 , 18 , 29 ]. For instance, Xu et al conducted a multi-center retrospective analysis of 1,499 rheumatoid arthritis (RA) patients, and determined that SIRI is significantly related to the disease activity of RA, even can predict the tumor development of RA individuals [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al analyzed 1,724 patients exhibiting acute coronary syndrome over a median follow-up of 927 days, and displayed SIRI to be independently predictive of major adverse cardiovascular events [ 16 ]. Another recent retrospective study recruited 526 individuals diagnosed as ischemic stroke proposed that SIRI is an independent predictor of AF [ 18 ]. However, the association between SIRI and NOAF in STEMI patients after PCI remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation